In vitro pharmacological properties of an indigenous medicinal plant, Artabotrys crassifolius Hook.f. & Thomson (Family: Annonaceae Juss.) - Tan, Kok Kwan (2015)
The tropical rainforest of Malaysia is considered as one of the most evolved and complex ecosystems in the world that serves a vast untapped biodiversity of natural resources. Exploitation of medicinal plants for bioactive compounds is of great potential and could be an imperative source of providing new vistas for novel drug discovery and development. The study was undertaken to evaluate the in vitro pharmacological properties of Artabotrys crassifolius including antibacterial, antifungal, anticancer and antioxidant activities of the plant. The leaves and bark of Artabotrys crassifolius were extracted sequentially using hexane, chloroform and ethanol. The prepared crude extracts were subjected to phytochemical screenings for the presence of alkaloids, cardiac glycosides, flavonoids, phenolic compounds, saponins, tannins and terpenoids. Kirby-Bauer disc diffusion assay was conducted to examine the antibacterial and antifungal activities of crude extracts against ATCC and clinical strains. The anticancer effect of crude extracts was investigated against human breast and colorectal carcinoma cell lines using MTT assay whereas the antioxidant potential of crude extracts was assessed using TPC, TFC, ABTS, DPPH and FRAP assays. Among the crude extracts studied, hexane and chloroform extracts of bark exhibited pronounced antibacterial activities against ATCC and clinical strains with zones of inhibition ranging from 8.23±0.25 mm to 13.70±0.26 mm and 7.75±0.25 mm to 13.68±0.28 mm respectively. However, all the crude extracts were found to be devoid of antifungal activity except for hexane extract of bark which was able to inhibit the growth of the tested Candida species with zones of inhibition ranging from 7.81±0.27 mm to 9.77±0.25 mm. In addition, chloroform extract of bark was highly active against all of the tested carcinoma cell lines with GI50 values ranging from 4.23 µg/mL to 9.45 µg/mL, while hexane extract of bark potently inhibited the growth of MDA-468 breast and HCT-116 colorectal carcinoma cell lines with respective GI50 values of 6.10 µg/mL and 16.45 µg/mL. Furthermore, ethanol extract of bark that possessed the highest total phenolic and flavonoid contents (268.29±12.36 mg GAE/g and 179.54±4.98 mg CE/g) was shown to demonstrate prominent scavenging activities against ABTS cation and DPPH radicals with IC50 values of 16.50 µg/mL and 16.54 µg/mL respectively, as well as exceptionally high antioxidant power with FRAP value of 1884.35±83.78 µmol Fe(II)/g. The chromatographic separation of chloroform extract of bark led to the isolation of four alkaloids, namely artabotrine, liridine, atherospermidine and lysicamine. Among the compounds isolated, artabotrine displayed high antibacterial properties with respective MIC and MBC values ranging from 1.25 µg/mL to 5 µg/mL and 1.25 µg/mL to 20 µg/mL against all of the tested ATCC and clinical bacterial strains, with the exception of Actinobacillus sp. and Klebsiella sp.. Moreover, artabotrine was highly active in HCT-116 colorectal and MCF-7 breast carcinoma cell lines with GI50 values of 3.34 μM and 3.49 μM respectively. In conclusion, exploration of the in vitro pharmacological properties of Artabotrys crassifolius revealed that artabotrine with dual antibacterial and anticancer activities may represent a new generation of potential drug candidates for the treatment of bacterial infections and cancer. Hence, further in vivo studies and clinical trials are required to ascertain the efficacy, safety and mechanisms of action of artabotrine prior to application in the pharmaceutical industry as natural therapeutic agents.